2014
DOI: 10.1080/10803548.2014.11077030
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Shift Work Schedules and Spillover in a Sample of Nurses

Abstract: The aim of the present study was to estimate spillover effects between the work and the family sphere in a sample of nurses (N = 2058). Hierarchical regression analyses investigated whether shift work schedules were associated with negative or positive spillover, both from family to work and vice versa, controlling for demographic factors, job demands and decision latitude. With daytime work as a reference group, all types of shift work (day and evening shift, night shift only and rotating 3 shift) were associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…2008), sample characteristics such as age and sex (Saksvik et al, 2011), general working conditions (Costa, 2003), speed and direction of rotation (Knauth, 1995), shift start times (Sallinen and Hublin, 2015), and other sample characteristics such as work-family spillover (Kunst et al, 2014). Future studies should thus more stringently investigate predictors of SWD.…”
Section: Discussionmentioning
confidence: 99%
“…2008), sample characteristics such as age and sex (Saksvik et al, 2011), general working conditions (Costa, 2003), speed and direction of rotation (Knauth, 1995), shift start times (Sallinen and Hublin, 2015), and other sample characteristics such as work-family spillover (Kunst et al, 2014). Future studies should thus more stringently investigate predictors of SWD.…”
Section: Discussionmentioning
confidence: 99%
“…However, focusing on full and part-time working, Abrahamsen, Holte and Laine [29] showed that in both cases nurses expressed similar levels of WF interference. Also inconvenient work schedules-evening work, night work, weekend work, shift work (shift and night work, evening shift, rotating shifts), variable/flexible working time, pro-Open Journal of Medical Psychology longed duty periods-had been considered as important antecedents of WFC [30] [31]. In Italy, Camerino et al [32] found that quantitative workload, together with the performance of tasks not belonging to the nursing profession, and the number of weekends/month spent at work, were all strongly associated with WFC.…”
Section: Work-family Conflictmentioning
confidence: 99%
“…As well, Yildirim and Yacan (2008) observed that irregular work schedules and excessive workload, but not working hours or overtime, were associated with WFC. In another study by Kunst et al (2014), it was revealed that among Japanese nurses, negative WF spillover differed across work schedules (rotating work shift, day only, evening only, night only or day and evening). In a sample of Italian nurses, Camerino et al (2010) found that irregular day work and shiftwork with nights had the most adverse effects on WFC.…”
Section: Antecedents or Predictors Of Wfcmentioning
confidence: 98%